Haploid-specific variations of kiwifruit WAKL genes modulate immune-related responses in Nicotiana benthamiana - Zupeng Wang; Zhenting Sun; Hui Pan; Caihong Zhong; Li Li (Plant Stress)
Wall-Associated Kinase-like (WAKL) proteins play crucial roles in plant stress responses, but their evolutionary divergence and functions in kiwifruit remain unclear. In this study, we performed a genome-wide analysis of WAKL proteins in Actinidia chinensis and Actinidia eriantha. Our findings reveal haploid-specific variations that contribute to kiwifruit resistance against bacterial canker. Significant structural and numerical differences in WAKL genes between haploids were identified, driven by genomic rearrangements and duplication events. Phylogenetic and motif analyses revealed functional specialization and evolutionary divergence within the WAKL family in kiwifruit. Expression analysis showed that key WAKL genes respond differently in resistant and susceptible kiwifruit during Psa infection. We validated nine AcWAKL genes in Nicotiana benthamiana. Four induced reactive oxygen species (ROS) accumulation and cell death, and three of these genes are found only on one haploid. Further investigation showed that these four AcWAKL genes triggered ROS accumulation and cell death by upregulating NbRBOHB expression. Our findings highlight the importance of haploid-specific variations and PAVs in shaping WAKL gene function, providing new insights into how these genomic features modulate immune responses and offering potential implications for enhancing disease resistance in kiwifruit breeding.